Exploring C-To-G Base Editing in Rice, Tomato, and Poplar - Sretenovic, Simon; Liu, Shishi; Li, Gen; Cheng, Yanhao; Fan, Tingting; Xu, Yang; Zhou, Jianping; Zheng, Xuelian; Coleman, Gary; Zhang, Yong; Qi, Yiping (Frontiers in Genome Editing, 2021)
As a precise genome editing technology, base editing is broadly used in both basic and applied plant research. Cytosine base editors (CBEs) and adenine base editors (ABEs) represent the two commonly used base editor types that mediate C-to-T and A-to-G base transition changes at the target sites, respectively. To date, no transversion base editors have been described in plants. Here, we assessed three C-to-G base editors (CGBEs) for targeting sequences with SpCas9’s canonical NGG protospacer adjacent motifs (PAMs) as well as three PAM-less SpRY-based CGBEs for targeting sequences with relaxed PAM requirements. The analyses in rice and tomato protoplasts showed that these CGBEs could make C-to-G conversions at the target sites, and they preferentially edited the C6 position in the 20-nucleotide target sequence. C-to-T edits, insertions and deletions (indels) were major byproducts induced by these CGBEs in the protoplast systems. Further assessment of these CGBEs in stably transformed rice and poplar plants revealed the preference for editing of non-GC sites, and C-to-T edits are major byproducts. Successful C-to-G editing in stably transgenic rice plants was achieved by rXRCC1-based CGBEs, pYPQ265O1 and pYPQ265O2, with editing efficiencies up to 38%. The UNG-rAPOBEC1 (R33A)-based CGBE (pYPQ265K) resulted in successful C-to-G editing in polar, with up to 6.25% editing frequency. Overall, this study revealed that different CGBEs have different preference on preferred editing sequence context, which could be influenced by cell cycles, DNA repair pathways, and plant species.